Large Scale Cathodic Exfoliation of Graphite Using Deep Eutectic Solvent and Water Mixture - Pavez-Irrazabal, J; Pavez-Irrazabal, J (Taylor and Francis Inc., 2018)
A short-time and low-cost synthesis route was used to produce large lateral size (from 2 to 15 μm) from monolayers to few layers of graphene by a two-step process of electrochemical exfoliation with a deep eutectic solvent in a mixture with water that can be reused, and ultrasonic bath. The graphene was characterized by SEM, TEM, AFM, Raman and electrochemical activity. During the electrochemical exfoliation, high expanded graphene particles were obtained and these were dispersed in a mixture of water with 5%wt ethylene glycol by an ultrasonic bath in order to complete the exfoliation process. An enhancement of the electrical conductivity of these dispersions was obtained with the increase of graphene concentration, 0.38 mg/mL, which best result was achieved with 30 wt% water and a DC voltage of 10 V. It was possible to add a conductive layer to a glass substrate with the graphene obtained and Tyndall effect was observed. © 2018 Taylor & Francis Group, LLC.